KUALITAS PELAYANAN KARYAWAN DISABILITAS MELALUI KOMUNIKASI NONVERBAL DI SUNYI COFFEE TERHADAP KEPUASAN PELANGGAN - Ade Paulina; Susi Andrini (ADISAM PUBLISHER, 2026)
Verbal and nonverbal communication are sometimes used simultaneously in certain situations. Nonverbal communication also plays a role in reinforcing or replacing verbal messages. Nonverbal communication is communication that uses body movements and facial expressions. Service quality is an activity carried out in real terms in establishing relationships between employees and their customers. Of course, in this service, communication is a crucial part of a relationship to interact with each other, both verbally and nonverbally. Some people can interact using verbal language, while others use nonverbal language, as found at Sunyi Coffee, which has its own uniqueness. Sunyi Coffee is a cafe that employs people with disabilities such as deaf (unable to hear) and mute (unable to speak/mute). The concept carried by Sunyi Coffee is to respect and provide support to people with disabilities. This study aims to determine, understand, and analyze the extent to which the quality of Sunyi Coffee employee service affects customer satisfaction. The research method used is a quantitative method with a positivist paradigm. The population was taken from 40.800 followers of the Instagram account @Sunyi Coffee and obtained a sample of one hundred people using the Slovin formula. Data collection was conducted by distributing questionnaires to one hundred respondents via Google Forms. The sampling technique used purposive sampling, based on the criteria that participants must be followers of @sunyi Coffee and have visited Sunyi Coffee more than once. Data processing was performed using SPSS calculations. The results of this study indicate that the quality of service provided to Sunyi Cof’fee's disabled employees has a strong positive influence on customer satisfaction.